Strategies to reduce joint load in the medial compartment of the knee during gait in individuals with osteoarthritis: a review of the literature - Claudio Marcos Bedran de Magalhães; Renata Noce Kirkwood
Abstract Introduction: Increased joint load on the medial compartment of the knee during gait is a mechanical factor responsible for pain and progression of medial knee osteoarthritis. The knee external adductor moment of force is a kinetic parameter that correlates with the joint load in the medial compartment. Objective: The aim of this study was to conduct a narrative review of the biomechanics strategies during gait of individuals with medial knee osteoarthritis that reduce external adductor moment of force of the knee. Methods: The review of the literature was conducted in the databases MEDLINE, PUBMED and PEDro and included articles published between 2000 and 2011. It was selected transversal, theoretical, correlational and longitudinal studies as well as controlled clinical trials. Results: Decreased gait velocity, increased external rotation of the foot, increased internal abductor moment force of the hip and lateral trunk inclination to the side of the support limb are compensatory strategies used to reduce the external adductor moment of force of the knee during gait of individuals with medial knee osteoarthritis. The lateral trunk inclination may be beneficial in a short term, however it decreases the activity of the abductors muscles of the hip during the support phase of the gait favoring compensation that could result in the progression of medial knee osteoarthritis. Conclusion: Strengthening of the abductors muscles of the hip reduces pain, improves the function and prevents compensations that in a long term could possibly accelerate the progression of the medial knee osteoarthritis.